Indocyanine green-mediated photothermal therapy in treatment of chronic periodontitis: A clinico-microbiological study - Chetan Purushottam Raut; Kunal Sunder Sethi; Bhagyashree Rajendra Kohale; Alefiya Mamajiwala; Ayushya Warang (Journal of Indian Society of Periodontology, 2018)
Background: Photodynamic therapy (PDT) has developed as an alternative treatment modality in periodontitis patients. Different photosensitizers used over the years have shown contradictory results. Thus, recently indocyanine green (ICG)-mediated photothermal therapy has emerged for the treatment of chronic periodontitis. Aim: The present study aimed at comparing and evaluating the effects of photothermal therapy using ICG in the treatment of chronic periodontitis with scaling and root planing (SRP). Materials and Methods: This was a randomized, controlled, clinical trial where fifty participants were equally divided into two groups, i.e., control group (SRP) and test group (SRP + photothermal therapy). Clinical parameters were evaluated at baseline and 6-month follow-up. These were plaque index (PI), bleeding on probing (BOP), probing depth (PD), and clinical attachment level (CAL). Microbiological analysis of plaque sample was also done to check for anaerobic mixed flora. Results: Significant reduction was seen in PD, CAL, and BOP in the test group as compared to control group after 6 months (P < 0.05). However, intergroup comparison of PI showed nonsignificant results (P > 0.05). Anaerobic culture of plaque samples of test group also revealed a significant reduction of microorganisms in comparison with control group. Conclusion: ICG-mediated photothermal therapy can act as an alternative to antimicrobial PDT as an adjunct to SRP in the treatment of chronic periodontitis.